Fate of preoperative moderate mitral regurgitation following left ventricular assist device implantation. Issue 6 (18th February 2021) - Tang, Paul C.; Duggal, Neal M.; Haft, Jonathan W.; Aaronson, Keith D.; Pagani, Francis D.
Abstract: Objective: We examined for improvements in preoperative moderate mitral regurgitation following continuous‐flow left ventricular assist device (cfLVAD) implantation. Methods: From 2006 to 2020, 190 patients with moderate MR underwent cfVLAD implant without concomitant mitral valve (MV) surgery. Cardiac dimensions and contractility, as well as valve function, were assessed with an echocardiogram (echo) pre‐cfLVAD, and at approximately 1 month post‐cfLVAD. Outcomes were determined by retrospective chart review. Results: Median echo follow‐up was 0.94 (0.53, 1.38) months. Residual significant moderate or greater MR was present in 30/190 (15.8%) on follow‐up. Patients with significant residual MR had larger preoperative left ventricular internal diameters in diastole (74.4 ± 8.7 vs. 71.1.0 ± 9.1 mm, p = .034). Significant residual MR was associated with higher preoperative mean pulmonary artery pressures (OR = 1.055, p = .035) and pulmonary capillary wedge pressures (OR = 1.060, p = .034). Significant residual MR on echo was not associated with any survival difference ( p = .325). The 1, 5, and 10 year survival were 89.9%, 55.2%, and 34.2%, respectively. Conclusions: For patients with moderate MR undergoing LVAD implantation, the likelihood of significant residual MR is low and mitral intervention in this population is not recommended. However, select patients with larger preoperative left heart dimensions and pulmonary vascular pressures may be at risk for persistent residual MR.